2022
DOI: 10.15388/omee.2022.13.79
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Trading Volume and Market Returns: A VAR/Granger Causality Testing Approach in the Context of Saudi Arabia

Abstract: This paper investigates the relationship between trading volume and market returns in the Saudi stock market. Daily data of number of shares traded and TASI returns from 2010 till mid-2021 are used for the same. The Granger causality test reveals a unidirectional relationship from returns to volume. This is supported by the findings of the VAR test and the Impulse Response Function (IRF) test. Trading volume does not carry informational content and cannot predict prices. Returns do impact volume, but the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
1
7
1
1
Order By: Relevance
“…It does not offer reliable predictive information; it can forecast both the gain and loss at the same time. This finding confirms the studies of Wang (2014), Mpofu (2012), andAlhussayen(2022).…”
Section: Technical Analysis In the Nasdaq Stock Exchange Marketsupporting
confidence: 93%
See 2 more Smart Citations
“…It does not offer reliable predictive information; it can forecast both the gain and loss at the same time. This finding confirms the studies of Wang (2014), Mpofu (2012), andAlhussayen(2022).…”
Section: Technical Analysis In the Nasdaq Stock Exchange Marketsupporting
confidence: 93%
“…This conclusion contradicts Mahajan and Singh (2008). Karpoff (1987) confirmed that volume is positively related to the magnitude of the price change which also supports Mahajan and Singh (2008) and contradicts Alhussayen (2022). The specific studies on NYSE by Huang and Heian(2010) using the conventional method developed by Jegadeesh and Titman (1993) found there is a statistically abnormal return for higher volume.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…They concluded that when the price of crude oil went up, the trading volumes increased and a decline in the futures prices resulted in the shrinkage of volumes. Alhussayen (2022) tested the causality between trading volume and returns of the stock market in Saudi Arabia and concluded that volume does not cause returns, whereas there is causality flowing from previous period rates of returns to trading volume. Dimitrios and Tseriki (2022) studied the trading volume and price of five agricultural commodities and observed bidirectional predictability between volume and price movements.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Harga saham dan volume perdagangan saham umumnya memiliki hubungan positif yang saling memengaruhi (Karpoff, 1987). Menurut Jenings et al (1981 return memang memengaruhi volume perdagangan namun dampaknya bisa positif, negatif atau tidak signifikan yang diakibatkan oleh beragamnya informasi yang tiba di pasar secara bersamaan, sehingga investor tidak dapat menangkap esensi sebenarnya dari informasi tersebut (Alhussayen, 2022). Menurut Admati & Pfleiderer (1988), setiap pelaku pasar memiliki kemungkinan untuk menanggapi informasi dengan reaksi yang berbeda sesuai dengan preferensinya.…”
Section: Hasil Dan Pembahasanunclassified